Effect Local Microorganisms Coconut Pulp in Increasing The Resistance of Red Chilli Plants To Fungus Colletotrichum acutatum J.H. Simmonds - Asrul Rusadi, Raisa Rahmi Putri; Yulianty, Yulianty; Sri Wahyuningsih; Eti Ernawiati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The fungus Colletotrichum acutatum which often attacks chili plants causes anthracnose disease. Farmers generally use fungicides to control this disease. Continuous use of synthetic fungicides will have negative impacts. Plant extracts as an alternative to natural fungicides can be an appropriate and environmentally friendly choice. One of them is the use of Local Microorganisms (MOL). This research aims to determine the optimal concentration of coconut pulp MOL in increasing the resistance of red chilli plants to the fungus Colletotrichum acutatum that causes anthracnose disease. The study used a Totally Randomized Design (CRD) with 6 drugs, namely A (0 ml/water), B (5 ml/water), C (10 ml/water), D (15 ml/water), E (20 ml/water). ml/water), F (25 ml/water). There are four treatments each time. Information was broken down using ANOVA and continued with the Fair Genuine Contrast (BNJ) test at the 5% level (α = 5%). with a level of 5% (α = 5%). The results showed a significant effect on fungal colony diameter, germination period, plant height, plant incubation period, and disease severity. The best concentration of local coconut pulp microorganisms in inhibiting anthracnose disease was 25 ml/l water.